Dietary Modelling in Increasing Cardiorespiratory Resistance the Student of Education and Training Center - Rina Hasniyati; Defniwita Yuska; Zulkifli; Kasmiyetti; Edmon; Novelasari; Rapitos Sidiq (proceedinginternational, 2023)
The Sport Development Index (SDI) survey in 2006 reported that the fitness level of students in Indonesia tended to be low. Dietary factor is among the most important determinant for cardio-respiration resistance. This study aims to develop a dietary model to increase cardio- respiration resistance of athletes at Student Education and Training Center (SETC) in Padang, West Sumatra, Indonesia. This study used a cross sectional design. The population is all students of SETC as many as 77 people. According to the inclusion criteria, a sample of 46 people was obtained. Sampling is done by simple random sampling method. Primary data collection includes data on characteristics, cardiorespiratory resistance, energy intake, fe intake, and physical activity. Data were analyzed univariately uses descriptive statistical measures. Bivariate analysis uses the Pearson and the Spearman correlation test. The results obtained an average cardiorespiration resistance of 102.8, energy intake of 2957.9 kcal, carbohydrate intake of 447.8 grams, protein intake of 105.7 grams, fat intake of 85.9 grams, intake of fe 11, 5 grams and physical activity averaged 8,1. Pearson correlation test results had a significant relationship between energy intake, carbohydrate intake and fat intake with cardiorespiratory resistance (p <0.05). Multiple linear regression test obtained a model equation to increase cardiorespiratory resistance with one independent variable, Cardiorespiration resistance = 71,324 + 0.070 carbohydrate intake. After calculating the needs according to the type of exercise, a significant relationship was found between the needs and resistance of cardiorespiration. It is hoped that the results of the equation found and can be applied by SETC.